The effect of different concentration of copper and zinc toward the paddy (MR 220) growth performance and soil nutrient / Nurul Syuhadah Ahmad - Ahmad, Nurul Syuhadah (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L.) is a primary food source for the Asia population. Copper (Cu) is importance in metabolic process of paddy including photosynthesis. Insufficient amount of Cu will reduce the growth performance, grain content as well as spikelet sterility of paddy. Zinc (Zn) is therefore reduce the yield and maintained content of paddy grain. This study aims to access the effects combination of zeolite with Cu and Zn solution on paddy growth performance and soil chemical properties. The experiment was conducted at UITM Jasin using the CRD design. Result showed that increasing level of combination of zeolite with Cu and Zn in the soil are significantly different in the soil nutrient for potassium (K) at treatment three with 100ppm of Cu and Zn, for calcium (Ca) and magnesium (Mg) at treatment four with 150ppm of Cu and Zn, and phosphorus (P) at the treatment one. But there are is no significant different for the plant growth performance. This happen due to several factor such as not enough space for paddy growth, soil pH and amount of apply soil in pot are not enough.